PENGARUH OPINI AUDIT TERHADAP HARGA SAHAM DENGAN UKURAN KANTOR AKUNTAN PUBLIK SEBAGAI VARIABEL PEMODERASI - Nugrahani, Sulih; Ruhiyat, Endang (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2018)
The purpose of this research is to prove empirically the influence of audit opinions on stock prices. In addition, this research also examined the moderation role of the size of the Public Accounting Firm on the relationship of audit opinion with stock prices. This research uses profitability and liquidity control variables. Companies studied are manufacturing companies listed on the Indonesia Stock Exchange 2012-2015.Sampling method used is purposive sampling method and obtained 63 companies that become the object of research. The data used are financial reports and independent auditor's reports published through www.idx.co.id and the list of stock prices through www.sahamok.com. The research hypothesis was tested using multiple linear regression analysis technique with moderated regression analysis (MRA).Based on the test results show that the audit opinion does not significantly affect the stock price. This study also shows that the size of Public Accounting Firm has no moderating on the relationship of audit opinion with stock price.